Dukungan Terhadap Anggota Keluarga Lansia dalam Melayani - Agustin Soewitomo Putri (EPIGRAPHE: Jurnal Teologi dan Pelayanan Kristiani, 2017)
This research purposed to show the category level of family supported to the aged people in church ministry at Gereja Bethel Injil Sepenuh Kepunton, Surakarta, year 2016. Hypotheses of this research is: a category level of family’s support to the aged people in church ministry is at Gereja Bethel Injil Sepenuh Kepunton, Surakarta, year 2016 is moderate. Analysis of correlation showed that family supported had a correlation level to the involvement of aged people in ministry is at 0.461, which means moderate. Though the hypotheses was tried and true, there were some recommendations to increase family supported to the aged people in ministry, like: making a seminar about family, special sermon’s theme about family or special retreat for aged people